Synopsis: Children’s diets, nutrition knowledge, and access to markets - Hirvonen, Kalle; Hoddinott, John F.; Minten, Bart; Stifel, David (International Food Policy Research Institute, 2016)
Chronic undernutrition in Ethiopia is widespread and many children consume highly monotonous diets. To improve feeding practices in Ethiopia, a strong focus in nutrition programming has been placed on improving the nutrition knowledge of caregivers. In this paper, we study the impact of improving nutrition knowledge within households and its complementarity with market access. To test whether the effect of nutrition knowledge on children’s dietary diversity depends on market access, we use survey data from an area with a large variation in transportation costs over a relatively short distance. This allows us to carefully assess the impact of households’ nutrition knowledge with varying access to markets, but still within similar agro-climatic conditions. We find that nutrition knowledge leads to considerable improvements in children’s diets, but only in areas with relatively good market access.